URGENSI PENDIDIKAN AGAMA ISLAM DALAM PENGEMBANGAN NILAI-NILAI MULTIKULTURAL - Wati, Salmiwati (AT-TALIM, 2013)
The function of Islamic education as one of compulsory subjects is to form the studentsâ character in order to be obedience and tolerance muslims. Thus, they can accept multicultural system and reject any form of oppresses because of diversity. It can be specifically seen from the objective of the lesson which aims to create Indonesian citizens to beÂ  diligent worshipers,Â  good ,Â  knowledge, intelligent, honest, wise, discipline, and tolerance muslims. They also should keep the harmony and develop religion and culture in the schools.